Talent Management: Malaysian Public Universities Vs Private Industries - Aniah Baharom (Journal of Human Development and Communication (JoHDeC), 2025)
Talent management has been lauded by literature as an effective method for organisations to remain competitive and sustainable. This paper is a reflective study on talent management practices in private industries compared to the general norm in Malaysian Public Universities. Literature search for this paper found that in industries, talent management is an organisation-wide effort and has the full involvement of every level in the organisation. However, although Public Universities use talent management for capacity building, to retain and attract talents, the approach in public universities differ from industries. Talent management is found to work effectively and achieve expected results when carried out properly. There must be clarity of vision and strategic direction, recognition of what talent management deliverables are and periodic review and evaluation methods before effective implementation of talent management can be achieved.